Syntaxin of plants71 plays essential roles in plant development and stress response via regulating pH homeostasis - Zhang, Hailong; Zhou, Jingwen; Kou, Xiaoyue; Liu, Yuqi; Zhao, Xiaonan; Qin, Guochen; Wang, Mingyu; Qian, Guangtao; Li, Wen; Huang, Yongshun; Wang, Xiaoting; Zhao, Zhenjie; et al. (Frontiers in Plant Science, 2023)
SYP71, a plant-specific Qc-SNARE with multiple subcellular localization, is essential for symbiotic nitrogen fixation in nodules in Lotus, and is implicated in plant resistance to pathogenesis in rice, wheat and soybean. Arabidopsis SYP71 is proposed to participate in multiple membrane fusion steps during secretion. To date, the molecular mechanism underlying SYP71 regulation on plant development remains elusive. In this study, we clarified that AtSYP71 is essential for plant development and stress response, using techniques of cell biology, molecular biology, biochemistry, genetics, and transcriptomics. AtSYP71-knockout mutant atsyp71-1 was lethal at early development stage due to the failure of root elongation and albinism of the leaves. AtSYP71-knockdown mutants, atsyp71-2 and atsyp71-3, had short roots, delayed early development, and altered stress response. The cell wall structure and components changed significantly in atsyp71-2 due to disrupted cell wall biosynthesis and dynamics. Reactive oxygen species homeostasis and pH homeostasis were also collapsed in atsyp71-2. All these defects were likely resulted from blocked secretion pathway in the mutants. Strikingly, change of pH value significantly affected ROS homeostasis in atsyp71-2, suggesting interconnection between ROS and pH homeostasis. Furthermore, we identified AtSYP71 partners and propose that AtSYP71 forms distinct SNARE complexes to mediate multiple membrane fusion steps in secretory pathway. Our findings suggest that AtSYP71 plays an essential role in plant development and stress response via regulating pH homeostasis through secretory pathway.